2021
DOI: 10.1186/s12967-020-02682-5
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ROR recruits histone transmethylase MLL1 to up-regulate TIMP3 expression and promote breast cancer progression

Abstract: Background As a significant cause of cancer deaths worldwide, breast cancer continues to be a troublesome malignancy. Long non-coding RNAs (lncRNAs) have been implicated in the development of breast cancer. Abnormal methylation has been associated with unfavorable breast cancer prognosis. Herein, the current study aimed to elucidate the role of lncRNA ROR in breast cancer. Methods RT-qPCR was performed to determine whether lncRNA ROR was highly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The recruitment of SUV39H1 triggers H3K9 methylation of human hyaluronidase family member PH20 and inhibits breast cancer growth and metastasis [ 103 ]. Being overexpressed in breast cancer tissues, lncRNA ROR promotes breast cancer progression via repression of transmethylase mixed-lineage leukemia 1 (MLL1) and tissue inhibitors of metalloproteinase 3 (TIMP3) [ 72 ] Dual-luciferase report assay and investigation of both cell lines and samples of patients with acute lymphoblastic leukemia confirmed that miR-137 directly targets lysine-specific demethylase JARID1B mRNA, leading to abnormal levels of H3K4me3 and H3K4me2 [ 86 ].…”
Section: Histone Modifications and Ncrnas: The Theorymentioning
confidence: 99%
“…The recruitment of SUV39H1 triggers H3K9 methylation of human hyaluronidase family member PH20 and inhibits breast cancer growth and metastasis [ 103 ]. Being overexpressed in breast cancer tissues, lncRNA ROR promotes breast cancer progression via repression of transmethylase mixed-lineage leukemia 1 (MLL1) and tissue inhibitors of metalloproteinase 3 (TIMP3) [ 72 ] Dual-luciferase report assay and investigation of both cell lines and samples of patients with acute lymphoblastic leukemia confirmed that miR-137 directly targets lysine-specific demethylase JARID1B mRNA, leading to abnormal levels of H3K4me3 and H3K4me2 [ 86 ].…”
Section: Histone Modifications and Ncrnas: The Theorymentioning
confidence: 99%
“…Fu et al ( Fu et al, 2017 ) reported that overexpression of miR-21 could inhibit granulosa cells apoptosis by inhibiting the expression of PDCD4. Tissue inhibitor of metalloproteinase-3 (TIMP3) has been reported to suppress the metastasis of glioma cells and breast cancer cells ( Hu et al, 2021 ; Wei et al, 2021 ). MMP2 is a downstream gene of TIMP3 and affects keratinocyte migration by degrading the extracellular matrix ( Caley et al, 2015 ; Lazaro et al, 2016 ).…”
Section: Overview Of Mir-21mentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a new class of epigenetic regulators that play important roles in several diseases, including cancer. Long non-coding RNA reprogramming (lncRNA-ROR) was shown to recruit the transmethylase MLL1 to promote H3K4 trimethylation that enhanced TIMP3 transcription [24].…”
Section: Epigenetic Regulationmentioning
confidence: 99%